PENCIPTAAN GAMBAR ILUSTRASI DARI NILAI NILAI MODERASI BERAGAMA - yusup, ikhsanudin; Haryana, Warli (Acintya, 2022)
The Indonesian nation is a rich nation that has a variety of cultures with their plural nature. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. In such a multicultural society, tensions and conflicts often occur between cultural groups and have an impact on the harmony of life. Religious moderation is very much needed in diversity and the role of religious educators in realizing national peace, so that it is hoped that it can create peace and peace for the Indonesian nation. Therefore, the author wants to campaign for the values of religious moderation through the media of illustration images which are expected to educate the importance of religious moderation for the community.Keywords: religious moderation, illustration images, media